Focused ultrasound influence on calcein-loaded thermosensitive stealth liposomes. (June 2015) - Novell, Anthony; Al Sabbagh, Chantal; Escoffre, Jean-Michel; Gaillard, Cédric; Tsapis, Nicolas; Fattal, Elias; Bouakaz, Ayache
Abstract Focused ultrasound (FUS) is a versatile technology for non-invasive thermal therapies in oncology. Indeed, this technology has great potential for local heat-mediated drug delivery from thermosensitive liposomes (TSLs), thus improving therapeutic efficacy and reducing toxicity profiles. In the present study we evaluated the influence of FUS parameters on the release of calcein from TSLs used to model a hydrophilic drug. Quantitative calcein release from TSLs (DPPC/CHOL/DSPE-PEG2000: 90/5/5) and non-thermosensitive liposomes (NTSLs) (DPPC/CHOL/DSPE-PEG2000: 65/30/5) was measured by spectrofluorimetry after both water bath and FUS-induced in vitro heating. The heating of TSLs at 42 °C in a water bath resulted in a maximum calcein release of 45%. No additional calcein release was observed at temperatures above 42 °C. A similar percentage of calcein release was achieved when TSLs were exposed to 1 MHz sinusoidal waves at peak negative pressure of 1.5 MPa, 40% duty cycle, for 10 min (i.e. above 42 °C). No release was detected when NTSLs were heated in a water bath. For both TSLs and NTSLs, the calcein release was increased by more than 10% for acoustic pressures ranging from 1.5 MPa to 2 MPa. This additional release was attributed to the mechanical stress generated by FUS, which was sufficient to disrupt the liposomal membrane. Furthermore, analysis of cryo-TEM images showed a significant decrease in liposome size (14%) induced by the thermal effect, whereas the liposome diameter remained unaffected by the FUS-triggered non-thermal effects.